Characterizing atmospheric aerosols using polarimetry and shadow hiding - Zubko, Evgenij; Zheltobryukhov, Maxim; Chornaya, Ekaterina; Shmirko, Konstantin A.; Lisitsa, Vladimir V.; Pavlov, Andrey N.; Kochergin, Anton; Kornienko, Gennady; Videen, Gorden (Frontiers in Remote Sensing, 2024)
Unpolarized sunlight is scattered by aerosols acquiring partial linear polarization. By aiming a ground-based detector vertically upward, it can record the polarimetric response of aerosols that are illuminated by the Sun. As the Sun sets, a portion of the sky is shadowed and the polarimetric response of the aerosols in the unshadowed region can be measured. This provides a means of scanning different portions of the atmospheric column with time. By comparing the measured polarimetric response with that of model agglomerated debris particles we can place constraints on the sizes and chemical composition of the aerosols in different portions of this column. We conducted a survey over 24 different epochs from April, 2021 to December, 2022, consisting of some ~600 measurements of polarization of the atmosphere in twilight at the Ussuriysk Astrophysical Observatory. We found that most of the measurements correspond with water-ice particles or dust. However, on some occasions organic carbon dominated the measurements. These epochs correspond with increased fire seats in the region.